Criminal Accountability Of State Officials Committing Political Corruption In Indonesia - Yuliana Yuliana; Mujiono Hafidh Prasetyo (Arena Hukum, 2022)
Political corruption is a form of violation of people's human rights and is a worrying phenomenon because it is dominated by state officials who have superior positions. This article aims to find out how the reality of law enforcement against corruption is carried out by state officials and how the criminal responsibility of state officials who commit political corruption in Indonesia. This article uses a normative juridical method. The results shows that law enforcement against state officials who commit political corruption has not been carried out optimally. The low demands of prosecutors followed by judges' verdicts against state officials who commit corruption are the cause of the difficulty of eradicating this crime. The imposition of a maximum criminal threat or life imprisonment for perpetrators of political corruption is something that should be done to create a deterrent effect for the perpetrators or the public who see it. In this case, law enforcement officers must have the courage, integrity, and high morale to be indiscriminate in eradicating political crimes in Indonesia.